The new primal blueprint : reprogram your genes for effortless weight loss, vibrant health, and boundless energy - Sisson, Mark, 1953- (Primal Blueprint Publishing, 2017)
A comprehensive guide to promoting optimal gene expression and longevity, honoring the evolutionary health model through 10 diet, exercise and lifestyle laws.